2014
DOI: 10.1016/j.proeng.2014.06.305
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-breaking Bifurcations in T-channel Flows: Effects of Fluid Viscoelasticity

Abstract: It is well known that, beyond a critical aspect-ratio-dependent Reynolds number, the flow in a three-dimensional T-channel junction, i.e. two-opposing planar channel streams joining and turning through 90 degrees, can break symmetry. For the case of two square cross-section inlets and an outlet arm of equal area (i.e. aspect ratio of two) this bifurcation is to a steady asymmetric flow. This flow bifurcation has been proposed as a method of enhancing mixing in microfluidic channels where significant increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…10 and the reduction in critical Reynolds number with increasing polymer concentration reported for the onset of EIT by Samanta et al [4], although the onset Reynolds number for vortex formation in the cross slot is around 2 orders of magnitude smaller than that for EIT. The critical Reynolds number for the onset of inertioelastic flow instabilities in T-shaped intersecting channels with two inlets of aspect ratio α ¼ 1 and one outlet of α ¼ 2 has also been found to be dependent on El [80]. In the Newtonian case, flow in such channels becomes unstable, resulting in the formation of vortices extending along the outlet channel when the Reynolds number exceeds a critical value Re c ≈ 100 [53,54,81].…”
Section: Detailed Analysis and Phase Diagramsmentioning
confidence: 96%
See 2 more Smart Citations
“…10 and the reduction in critical Reynolds number with increasing polymer concentration reported for the onset of EIT by Samanta et al [4], although the onset Reynolds number for vortex formation in the cross slot is around 2 orders of magnitude smaller than that for EIT. The critical Reynolds number for the onset of inertioelastic flow instabilities in T-shaped intersecting channels with two inlets of aspect ratio α ¼ 1 and one outlet of α ¼ 2 has also been found to be dependent on El [80]. In the Newtonian case, flow in such channels becomes unstable, resulting in the formation of vortices extending along the outlet channel when the Reynolds number exceeds a critical value Re c ≈ 100 [53,54,81].…”
Section: Detailed Analysis and Phase Diagramsmentioning
confidence: 96%
“…In the Newtonian case, flow in such channels becomes unstable, resulting in the formation of vortices extending along the outlet channel when the Reynolds number exceeds a critical value Re c ≈ 100 [53,54,81]. There are rather few numerical or experimental studies of non-Newtonian flows in T channels [80,[82][83][84]. However, using the upperconvected Maxwell model, Poole et al showed numerically that low levels of fluid elasticity could cause a reduction in Re c [80].…”
Section: Detailed Analysis and Phase Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that in the range of similar Re and Wi numbers where forward bifurcation usually occurs, forward Hopf bifurcation was observed instead, and the existence of the long recirculating cavity played a decisive role. Poole et al numerically investigated the effects of aspect ratio and shear-thinning properties for generalized Newtonian fluid [ 48 ] and viscoelasticity [ 49 ] on the symmetry-breaking bifurcations in T-channel flows. A common feature of the above studies is that two streams collided head-on from two opposite entrances and then evacuated through 90 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Branching of pipes occurs in many technical or biological applications. In [13] the effects of viscoelasticity on the pitchfork bifurcation using a numerical finite volume method was investigated. Results from both the upper-convected Maxwell and Oldroyd-B models show that the instability occurs at lower Reynolds numbers for viscoelastic fluids in comparison to the Newtonian base case.…”
Section: Introductionmentioning
confidence: 99%